(untitled) (Móin-Móin Magazine - Studies in the Art of Puppetry, 2018)
Lepage’s theatricality functions within the combination of live and recorded imagery, it is a communication between performers and all the technology invited into the space, where in Johannes Barringer’s terms, ‘spatial perceptions are made through what is physically introduced into space.’ Technology is also, as Alison Oddey observes, contributing to the process of creation in devised theatre and influencing the development of the performance in its evolution. Lepage likes to relate to technology at the same level as to the written text (when there is one), and performers’ creativity. This collage of live and recorded could be referred to as techno-en-scene, or technology that is in symbiosis with performer’s action in space. Indeed, Lepage’s techno –en-scene is hybrid theatricality that combines live performance with cinematic imagery, video and slide projections, and collaborations with digital technologies and artists from various disciplines.